UAV Mapping for Flood Routing in Steep and Densely Vegetated Areas: Insights from the Contok River Basin, Garang Watershed, Indonesia - Hanafi, Fahrudin; Kurniawan, Edi; Priakusuma, Dwi; Kubiak-Wojcicka, Katarzyna (BRIN Publishing, 2024)
This research utilizes photogrammetry to assess flood routing dynamics in the Contok river basin, a sub-watershed with a challenging landscape characterized by steep slopes, dense vegetation, and meandering patterns. The objectives are to assess Unmanned Aerial Vehicle (UAV) mapping accuracy, evaluate the river's capacity for design flood volumes, quantify the impact of land cover changes on surface runoff, and provide insights for early warning systems and watershed conservation strategies. The study area, encompassing the Contok River Basin, a sub-watershed of the Garang Watershed, covers 7,413 km² and includes a stream length of 5,274 meters in Semarang City, Central Java, Indonesia. This research employed image processing of aerial photographs and satellite imagery. Aerial photos captured using UAV data were utilized to derive elevation data and cross-sectional profiles of the Contok River, essential for understanding channel morphology and hydraulic characteristics. Concurrently, satellite imagery was used for land cover analysis, identifying vegetation and built-up areas that influence surface runoff dynamics. Hydrological analysis was performed to quantify discharge magnitudes, simulated against river cross-sections to evaluate flood behavior under varying scenarios. Our proposed UAV mapping provides adequate accuracy for small and local areas. Furthermore, it remains reliable for flood routing analysis. We discovered that the capacity of the Contok River channel in the downstream area allows it to convey design flood discharges up to a 50-year return period, contrary to the upstream area, it overflows. Notably, the shift from vegetated to built-up and agricultural areas significantly contributes to the 10.6% increase in surface runoff. This research highlights the role of UAV-based photogrammetry in assessing and mitigating flood hazards amidst evolving land cover patterns. It also enhances the understanding of flood dynamics and thus provides insights that will serve as a reference for flood early warning systems, flood management practices, and watershed conservation.